Antitumor activity of genetically engineered NK-cells in non-hematological solid tumor: a comprehensive review - Dash, Chinmayee Priyadarsini; Sonowal, Dhruba; Dhaka, Prachi; Yadav, Rohit; Chettri, Dewan; Satapathy, Bibhu Prasad; Sheoran, Pooja; Uttam, Vivek; Jain, Manju; Jain, Aklank (Frontiers in Immunology, 2024)
Recent advancements in genetic engineering have made it possible to modify Natural Killer (NK) cells to enhance their ability to fight against various cancers, including solid tumors. This comprehensive overview discusses the current status of genetically engineered chimeric antigen receptor NK-cell therapies and their potential for treating solid tumors. We explore the inherent characteristics of NK cells and their role in immune regulation and tumor surveillance. Moreover, we examine the strategies used to genetically engineer NK cells in terms of efficacy, safety profile, and potential clinical applications. Our investigation suggests CAR-NK cells can effectively target and regress non-hematological malignancies, demonstrating enhanced antitumor efficacy. This implies excellent promise for treating tumors using genetically modified NK cells. Notably, NK cells exhibit low graft versus host disease (GvHD) potential and rarely induce significant toxicities, making them an ideal platform for CAR engineering. The adoptive transfer of allogeneic NK cells into patients further emphasizes the versatility of NK cells for various applications. We also address challenges and limitations associated with the clinical translation of genetically engineered NK-cell therapies, such as off-target effects, immune escape mechanisms, and manufacturing scalability. We provide strategies to overcome these obstacles through combination therapies and delivery optimization. Overall, we believe this review contributes to advancing NK-cell-based immunotherapy as a promising approach for cancer treatment by elucidating the underlying mechanisms, evaluating preclinical and clinical evidence, and addressing remaining challenges.